Perspektif Evolusi Teori Organisasi Bagi Organisasi di Masa Depan - Ahmad Muksin; Cindy Silalahi; Ressa Nur Cahya; Mohammad Syahrul Leo Febriansyah; Refina Mega; Nurul Ihsan Fauzan (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This research is used to answer two main problems, namely why the development of concepts in the field of organizational theory is a paradigm shift factor and why technological implications encourage progress in strategic integration in organizations in the future. The method used to complete this research is not field research, but rather a documentation method. The documentation method is a data collection technique by studying data that has been documented. The results of this research show that there are three different paradigms in an organization, namely the classical paradigm and the traditional paradigm. paradigm shift. These three differences have their respective positive and negative impacts. Possibilities that will emerge as inspirational technology develops are that workers communicate virtually, innovation and creation are normal things, always connected every day, job changes increase, focus on solutions, more precise decision making. There will be more and more existing paradigms and they will have their advantages and disadvantages each. Every existing paradigm has a goal towards change for the better, although not all of the results will have a good impact. By utilizing technology, an organization will gain many benefits in achieving organizational strategy. HR must keep up with the times so that existing organizations can always achieve their goals.